2021
DOI: 10.1299/mej.21-00127
|View full text |Cite
|
Sign up to set email alerts
|

Human interface design for semi-autonomous control of leader-follower excavator based on variable admittance and stagnation/trajectory bifurcation of nonlinear dynamics

Abstract: Conventional remote operation of an excavator has low work efficiency comparing with on-site operations. This is because it is difficult for an operator to recognize the excavator status and surrounding environments. Moreover, there are restrictions such as a limitation on the amount of information that can be transmitted, delays in communication, and harsh environments that cause sensor failure. Therefore, we have developed a semi-autonomous control system that consists of autonomy and human manipulation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the context of pHRI (Physical Human-Robot Interaction), Khoramshahi et al (2018) have proposed transforming the task trajectory using a cooperative robot to adapt a parameterized dynamic system to the human intended task online. However, no method has been proposed to combine task selection (as proposed in (Okada et al, 2021;Pistillo et al,2011;Khoramshahi et al, 2019)) and task trajectory deformation (as proposed in (Okada et al, 2020;Khoramshahi et al, 2018)) in nonlinear dynamics in a single robot to achieve operation separation. We contribute to these research areas by proposing a semi-autonomous leader-follower system that deforms the task trajectory in a nonlinear dynamical system with attractor and achieves operational separation between task selection and trajectory deformation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of pHRI (Physical Human-Robot Interaction), Khoramshahi et al (2018) have proposed transforming the task trajectory using a cooperative robot to adapt a parameterized dynamic system to the human intended task online. However, no method has been proposed to combine task selection (as proposed in (Okada et al, 2021;Pistillo et al,2011;Khoramshahi et al, 2019)) and task trajectory deformation (as proposed in (Okada et al, 2020;Khoramshahi et al, 2018)) in nonlinear dynamics in a single robot to achieve operation separation. We contribute to these research areas by proposing a semi-autonomous leader-follower system that deforms the task trajectory in a nonlinear dynamical system with attractor and achieves operational separation between task selection and trajectory deformation.…”
Section: Related Workmentioning
confidence: 99%
“…x = θ x y ϕ T is the state variable of each robot, θ is the turning angle, x and y are the position of the base of the bucket, ϕ is the absolute angle of the bucket, and the subscripts l and f represent leader and follower. This system is based on methods described in our previous paper (Okada et al, 2021), with the addition of the trajectory deformation elements described in Section 4. Full details of the methods used can be found in this previous paper.…”
Section: Block Diagram Of Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Aoi et al demonstrated the advanced turning maneuvers of a multilegged centipede robot using the bifurcation phenomenon as a parameter of the flexibility of its body segments [40]. In a study of bifurcated gait transitions, a semi-autonomous control system with two bifurcated attractors was proposed [41]. This robot motion transition exhibits an example of successfully using the stabilization and destabilization of a nonlinear dynamical system and is expected to realize highly efficient motion control because the system as a whole actively moves toward a stable state (attraction phenomenon).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on leader-follower robots aim at achieving "human-machine integration" control [6][7][8][9][10][11][12][13][14]. This approach emphasizes mirroring human motion in robot actions, which enables precise control.…”
Section: Introductionmentioning
confidence: 99%